Maternal glucose intolerance during pregnancy affects offspring POMC expression and results in adult metabolic alterations in a sex-dependent manner - Martins, Marina Galleazzo; Silver, Zachary; Ayoub, Kiara; Hyland, Lindsay; Woodside, Barbara; Kiss, Ana Carolina Inhasz; Abizaid, Alfonso (Frontiers in Endocrinology, 2023)
Gestational diabetes (GDM) is associated with negative outcomes in mothers and their offspring, including greater risks of macrosomia at birth and the development of metabolic disorders. While these outcomes are well-established, the mechanisms by which this increased metabolic vulnerability is conferred on the offspring are comparatively lacking. One proposed mechanism is that maternal glycemic dysregulation alters the development of hypothalamic regions related to metabolism and energy balance. To investigate this possibility, in this study, we first examined the effects of STZ-induced maternal glucose intolerance on the offspring on pregnancy day (PD) 19, and, in a second experiment, in early adulthood (postnatal day (PND) 60). Whether effects would be influenced by sex, or exposure of offspring to a high-fat diet was also investigated. The impact of maternal STZ treatment on POMC neuron number in the ARC of offspring at both time points was also examined. As expected, STZ administration on PD 7 decreased maternal glucose tolerance, increased risk for macrosomia, and loss of pups at birth. Offspring of STZ-treated mothers were also more vulnerable to develop metabolic impairments in adulthood. These were accompanied by sex-specific effects of maternal STZ treatment in the offspring, including fewer POMC neurons in the ARC of females but not males in late pregnancy and a higher number of POMC neurons in the ARC of both male and female adult offspring of STZ-treated dams, which was exacerbated in females exposed to a high-fat diet after weaning. This work suggests that maternal hyperglycemia induced by STZ treatment, in combination with early-life exposure to an obesogenic diet, leads to adult metabolic alterations that correlate with the increased hypothalamic expression of POMC, showing that maternal glycemic dysregulation can impact the development of hypothalamic circuits regulating energy state with a stronger impact on female offspring.